Analyzing the degradation of pre-damaged PV-modules - Buerhop, Claudia; Winkler, Thilo; Wirsching, Sven; Pickel, Tobias; Bemm, Andreas; Camus, Christian; Hauch, Jens; Brabec, Christoph (Proc. SPIE 10370, Reliability of Photovoltaic Cells, Modules, Components, and Systems X, 2017)
Cracked PV-modules are frequently detected in PV-systems. The impact of cracked cells on the energy yield and module performance under real operating conditions is not yet understood but of great relevance. Standard tests cannot reveal the relevant information conclusively. Therefore, we conducted a twofold analysis. 1) field exposure (global analysis on string level as well as detailed analysis on module level), and 2) load testing in the lab. Here, we present comparative electroluminescence (EL-) images recorded in an outdoor test stand and during load testing. Additionally, infrared (IR-) images as well as power data obtained from loaded and operating (field) conditions are discusse
Keywords: pre-cracked modules; field tests; loading tests; power measurements; IR-imaging; performance loss